Respuesta :

Answer:

I think it C

Step-by-step explanation:

Let's solve your equation step-by-step.

(k−4)2=9

Step 1: Simplify both sides of the equation.

k2−8k+16=9

Step 2: Subtract 9 from both sides.

k2−8k+16−9=9−9

k2−8k+7=0

Step 3: Factor left side of equation.

(k−1)(k−7)=0

Step 4: Set factors equal to 0.

k−1=0 or k−7=0

k=1 or k=7

Answer:

k=1 or k=7

Hope this helps! :)

Square both sides:

K -4 = sqrt(9)

With the answer being a square root rewrite with a postive and negative value:

K-4 = sqrt(9)

And

K-4 = -sqrt(9)

Simplify each:

K-4 = 3

And

K-4 = -3

Solving for k in each one you get answer

C. {1,7}